2010
DOI: 10.1111/j.1601-0825.2010.01656.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and distribution of SIBLING proteins in the predentin/dentin and mandible of hyp mice

Abstract: OBJECTIVES-Human X-linked hypophosphatemia (XLH) and its murine homologue, Hyp are caused by inactivating mutations in PHEX gene. The protein encoded by PHEX gene is an endopeptidase whose physiological substrate(s) has not been identified. Dentin matrix protein 1 (DMP1) and dentin sialophosphoprotein (DSPP), two members of the Small Integrin-Binding LIgand, N-linked Glycoprotein (SIBLING) family are proteolytically processed. It has been speculated that PHEX endopeptidase may be responsible for the proteolyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 62 publications
1
31
0
Order By: Relevance
“…It has also been suggested that PHEX is likely responsible for the cleavage of DMP1 and DSPP, as it has a strong preference for cleaving bonds at the N-terminal of these two SIBLING proteins . However, analysis of the Hyp mouse indicated no differences in Dmp1 and Dspp expression in comparison with their WT controls, suggesting that DMP1 and DSPP are in fact properly processed in the Phex-deficient mouse (Zhang et al 2010). In addition to this, there is an accumulation of SIBLING ASARM peptides in the Hyp mouse and patients, thus challenging the hypothesis that the SIBLING proteins are substrates for PHEX.…”
Section: The Asarm Hypothesis and Bone Diseasesmentioning
confidence: 59%
“…It has also been suggested that PHEX is likely responsible for the cleavage of DMP1 and DSPP, as it has a strong preference for cleaving bonds at the N-terminal of these two SIBLING proteins . However, analysis of the Hyp mouse indicated no differences in Dmp1 and Dspp expression in comparison with their WT controls, suggesting that DMP1 and DSPP are in fact properly processed in the Phex-deficient mouse (Zhang et al 2010). In addition to this, there is an accumulation of SIBLING ASARM peptides in the Hyp mouse and patients, thus challenging the hypothesis that the SIBLING proteins are substrates for PHEX.…”
Section: The Asarm Hypothesis and Bone Diseasesmentioning
confidence: 59%
“…It has been reported that the NH 2 -terminal fragments of DMP-1 localized to predentin and not mineralized dentin matrix in rat molar [21], indicating that it as an inhibitor of dentin mineralization. Zhang et al [22] demonstrated that DMP-1 N-terminal fragments were located not only in normal rat predentin, but also in widened areas of predentin in Hyp mouse. Therefore, another possible explanation for the formation of a large number of unmineralized areas in the dentin observed here is that amoxicillin injection may directly and/or indirectly affect the SIBLING family, including DMP-1, leading to disruption of dentin mineralization, as suggested by Boukpessi et al [20].…”
Section: Discussionmentioning
confidence: 98%
“…1) The forming alveolar bone cells originate from the neural crest, which is from the ectoderm, while the osteoblasts of the long bone are from the mesoderm. 2) The DSPP expression level in alveolar bone is much higher than in the long bone [19, 45]. 3) The alveolar bone defects in Dspp -null mice [28] are much more severe than the long bone defects [22], suggesting that DSPP’s role in alveolar bone formation is more important than in the long bone.…”
Section: Discussionmentioning
confidence: 99%